Performance assessment of optimized carbon-nanotube-based wireless on-chip communication - Franck, Pierre (2013)
We use 3D FEM simulation to study electrically-short carbon-nanotube-based antennas and their application to wireless on-chip communication. We first expose our model for single-wall carbon nanotubes and our simulation technique. This is then used to study extensively the various parameters involved in the design of a planar dipole antenna made of carbon nanotubes aligned over a quartz substrate. From this study, an appropriate design is selected and studied in an antenna-to-antenna transmission link.